Blockade of GITRL/GITR signaling pathway attenuates house dust mite-induced allergic asthma in mice through inhibition of MAPKs and NF-κB signaling. (September 2021) - Wang, Yaping; Liu, Bo; Niu, Chao; Zou, Wenjing; Yang, Lili; Wang, Ting; Tian, Daiyin; Luo, Zhengxiu; Dai, Jihong; Li, Qubei; Liu, Enmei; Gong, Caihui; et al.
Highlights: GITRL and GITR are highly expressed in HDM-induced asthma. GITRL/GITR-MAPK/NF-κB signaling pathway is activated in HDM-induced asthma. Knockdown of GITRL reduces allergic airway inflammation and airway hyperresponsiveness induced by HDM. GITRL knockdown inhibits the activation of GITRL/GITR-MAPKs/NF-κB signaling pathway. Abstract: GITRL/GITR signaling pathway plays an important role in allergy, inflammation, transplantation and autoimmunity. However, its role in asthma remains unclear. Thus, the present study aimed to investigate changes in this pathway and observe the therapeutic effect of its blocking on asthma. By using house dust mite-induced asthma model, changes of GITRL/GITR and its downstream molecules MAPKs (e.g., p38 MAPK, JNK and Erk) and NF-κB were observed. After that, GITRL in lung of mice was knocked down by recombinant adeno-associated virus to observe the impact on its downstream molecules and assess the therapeutic effect on asthma. These results showed that GITRL/GITR and its downstream molecules MAPKs/NF-κB were activated in asthmatic mice. This activation was suppressed after GITRL knockdown, and allergic airway inflammation and airway hyperresponsiveness were alleviated. These results demonstrate that GITRL/GITR-MAPKs/NF-κB signaling pathway participates in the pathogenesis of asthma. Blockade of GITRL/GITR signaling pathway exhibits protective effects in a mouse model of house dust mite-induced allergic asthma.